Importance, Implementation and Limitation of Pharma Doctors in Clinical Pharmacy Practice for Out-patient Health Care Setting - Harikrishna, Allu (Journal of Pharmacy Practice and Community Medicine)
Pharma Doctors importance, Implementation and limitation for practicing clinical Pharmacy services for out-patient at the site of community Pharmacy. Clinical Pharmacy services were most important service for out-patients like DM, HTN, CKD, Psychiatric patients, CHD and co-morbidity Disease patients to avoid drug relevant problems for the safest and affective therapy. Providing a Disease and Medication knowledge, Drug and Poison information to the patents, Public and Health care Professionals. Aim: To the perform “Importance, Implementation and limitation of Pharma Doctors in Clinical Pharmacy Practice for Out-Patient Health care setting”. For providing safest effective prescription order. Clinical Pharmacy establishment at the site of community Pharmacy: Clinical Pharmacy Service is a part of dispensary service as interpretation, evaluation and implementation of prescription these service will give safest and effective therapeutic prescription base on these terms need to establish clinical Pharmacy in the site of Community Pharmacy. Conclusion: Clinical Pharmacy Service will help the patient to provide safest and effective therapeutic prescription and lowering the health economic burden, providing the best medication administration knowledge to the patient for avoiding medication non-adherence.
Keywords: Clinical Pharmacy; Community Pharmacy; Dispensing; safety and Effective therapy; Pharmaco-econamic efficacy; Pharmacy Practice regulation; Clinical establishment act; Pharmacy act; Drug and Poison information; Patient Counseling; Drug related Problems.